Stories That Heal: Reimagining Health Through African Literature and Tradition - Oladimeji, Anuoluwapo Omowale; Alao, Jude Oluwapelumi (Walter de Gruyter GmbH, 2025)
Health promotion in sub-Saharan Africa often has poor results because many interventions neglect local cultural frameworks. This paper reviews how African literature and storytelling, spanning oral traditions, novels, poetry and drama, can strengthen culturally grounded health communication. Interpreting narratives through the health belief model (HBM) and social cognitive theory (SCT), it examines how stories frame risk, model health behaviours and build collective efficacy. Drawing on works by Achebe, Ngũgĩ, p’Bitek, Soyinka and Bâ, alongside case studies of HIV, malaria and Ebola interventions, the analysis shows that storytelling can reduce stigma, enhance trust and inspire behavioural change. The paper recommends creating frameworks for integrating storytelling into health promotion, training health workers in narrative competence, and expanding research on its behavioural impact. African literature emerges as both an analytical and practical resource for culturally responsive, sustainable, public health strategies.
Keywords: 4704 Linguistics; 43 History, Heritage and Archaeology; 44 Human Society; 47 Language, Communication and Culture; 4303 Historical Studies; 4404 Development Studies; Infectious Diseases; Prevention; HIV/AIDS; 3.1 Primary prevention interventions to modify behaviours or promote wellbeing; Infection; 3 Good Health and Well Being; 1699 Other Studies in Human Society; 2004 Linguistics; 2099 Other Language, Communication and Culture; 4303 Historical studies; 4404 Development studies; 4704 Linguistics; African literature; cultural narratives; health promotion; public health interventions; storytelling